Vokametri: Mobile Application for Observation of Attitude Aspects Based on KKNI in Vocational Students - Wahyu Ridhoni; Tesdiq Prigel Kaloka; Danang Yugo Pratomo (Universitas Lambung Mangkurat, 2023)
Findings at Hasnur Polytechnic show that some aspects of attitude assessment still do not produce diverse scores. In one class, all students obtained the same grade. This problem arises because there are no guidelines for making observations. This research focuses on building a mobile app so that lecturers can more easily assess each learning session. The research method used as a framework in the development process is ADDIE (Analysis, Design, Development, Implementation and Evaluation). The result of this research is the Vokametri application, built with the Ionic framework for the Android platform. All functions of the application have worked well. Therefore, it can be used by lecturers to conduct KKNI-based attitude observations. This application works offline so that the assessment can be done without being connected to the internet. Lecturers can view student attitude score records and download Excel files that list the attitude scores of all students in a course.